2021
DOI: 10.1016/j.jcmgh.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Intestinal Sodium Transport in Inflammatory Bowel Disease: From the Passenger to the Driver's Seat

Abstract: We synthesize genetic and cellular evidence to construct a model proposing that impaired intestinal sodium transport can act as an upstream pathogenic factor in IBD. The model predicts that strategies designed to correct disturbed electrolyte homeostasis carry high therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 96 publications
(179 reference statements)
1
16
0
Order By: Relevance
“…Therefore, reduced NHE3 activity in the gut of patients with hyperactive GUCY2C mutations could contribute to the incidence of Crohn’s-like symptoms and colitis. We recently speculated that impaired intestinal sodium transport and its effects on the microbiome could serve as a major upstream mediator of downstream pathophysiology ( Prasad and Visweswariah, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reduced NHE3 activity in the gut of patients with hyperactive GUCY2C mutations could contribute to the incidence of Crohn’s-like symptoms and colitis. We recently speculated that impaired intestinal sodium transport and its effects on the microbiome could serve as a major upstream mediator of downstream pathophysiology ( Prasad and Visweswariah, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pathways not directly regulated by cGMP could also be misregulated in these mice, which, in turn, could feed back into the regulation of GC-C and its ligands. Since mice lacking Nhe3 display a susceptibility to DSS-induced colitis ( Kiela et al, 2009 ), electrolyte flux and imbalance in the intestine, coupled with alterations in the microbiome, may be the distal drivers of increased susceptibility to chemical-induced colitis ( Prasad and Visweswariah, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that the ionic milieu in the intestine plays a critical role in inducing gut inflammation and colitis (Prasad and Visweswariah, 2021). Impaired Na + and water transport, which occurs as a result of NHE3 deficiency, may mediate pathogenesis in gastrointestinal disorders such as CSD and IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of NHE3, a well-known effector, negatively regulated by GC-C, has also been linked to IBD-like pathologies in humans and mice models (57,114,115), indicating that the impairment of Na + absorption shared by both activating GC-C and inactivating NHE3 mutations could be a pathogenic driver in IBD. In line with this hypothesis, impaired sodium absorption is a long-recognized pathological feature in IBD and microscopic colitis, a poorly understood type of IBD that is nearly as common as CD and UC (16). Several studies have shown reduced NHE3 expression/activity in IBD patients and after exposure to proinflammatory cytokines and Clostridium difficile toxin B; however, it has been uncertain until recently whether the downregulation of NHE3 plays a causal role rather than simply reflecting the disease (116)(117)(118).…”
Section: Emerging Gc-c-directed Colorectal Cancer Therapiesmentioning
confidence: 98%